Presence of EGF ligand restricts the binding ability of EgB4 nanobody to EGFR extracellular domain - Duc Toan Truong; Mateusz Chwastyk; Viet Bac T. Phung; Minh Tho Nguyen (Scientific Reports)
Abstract EgB4 is a nanobody that could facilitate the development of drug–nanobody conjugates or drug delivery in cancer treatment due to its specific binding ability to the EGFR transmembrane protein. More significantly, EgB4 does not hamper the EGFR function and associates with EGFR in both the presence and absence of an EGF ligand. However, the difference in EgB4–EGFR interaction with and without EGF ligand is not clear. To explore this aspect, we carried out computations including classical molecular dynamics simulations, steered molecular dynamics simulations and the umbrella sampling method. The three main objectives of the study are: (i) how EgB4 interacts with EGFR, (ii) the role of an EGF molecule, and (iii) how to mutate EgB4 to efficiently construct a stronger nanobody. Our computed results showed that, in addition to the residues asp98 and asp110 that were previously reported, two other residues, arg105 and asp108, are also highly interactive with the EGFR extracellular domain. Notably, the absolute binding free energy of the EgB4–EGFR complex decreases from − 17.1 to -13.3 kcal/mol in going from an absence to a presence of EGF. With the EGF presence, the interacting space between both EgB4 and EGFR entities is also reduced. When EGF stabilizes the dimerization of EGFR, there is less opportunity for EgB4 to bind. This crucial aspect has not been reported before.